Physiological and mental condition of male university judoka during camp training period - Masuchi, K.; Kobayashi, Y.; Kanamaru, Y.; Ono, T.; Akimoto, H.; Norikane, S.; Ogura, D.; Matsui, T. (Association for the Scientific Studies on Judo, Kodokan, 2015)
Physical and mental conditioning through sports training is critical for achieving better competitive performance. However, the conditioning methods in judo training are largely unknown. To create basal data for the conditioning in judo training, we here examined the physiological and psychological conditions at a judo training camp in male university judokas. Twelve male university judokas were collected blood from the median antebrachial vein immediately after they awoke at 6 a.m., during and following the six days of judo training camp (the pre-camp, and the fourth and sixth day of camp, and the second and third days after the camp) . The blood was analyzed to detect Cortisol (a stress hormone that elicits muscle catabolism) , immunoglobulin A (IgA, an indicator of the immune System) , creatine kinase (CK, a muscle damage marker) , and free testosterone (a male sex hormone that induces muscle anabolism) . Psychological conditions were assessed with the Profile of Mood States (POMS) following the blood collection. Blood Cortisol and IgA were unchanged during and following camp, but CK, free testosterone, and the free testosterone-cortisol ratio were significantly increased on the fourth day of camp compared to pre-camp, but gradually decreased afterward. The POMS fatigue score at the fourth and sixth day of camp was significantly higher than that on pre-camp and recovered to pre-camp levels with one to two days of rest after camp. These results reveal that three days of judo training camp in male university judokas induces psychological fatigue and muscle damage while eliciting the physiological condition for muscle protein anabolism with increased free testosterone levels. Based on present findings, repetition of three days of judo training camp with one to two days of rest might contribute to optimum physical and mental conditions for inducing supercompensation-based training benefits in male university judokas.